Public Reason and a Pedagogy for Reasonableness - Lee, Zosimo E. (Archīum Ateneo, 2024)
John Rawls and Jürgen Habermas have undertaken a conversation on the meaning and significance of ‘public reason.’ This paper seeks out the main features of this conversation, and contends that the idea of the ‘community of inquiry’ in Philosophy for Children can respond to some of the concerns raised, as part of deliberative practice. Finally, it argues that for public reason to be created it is imperative that there be a pedagogy for reasonableness, following Matthew Lipman.